The assessment of the effects of genomic heterozygosity and sterility on the performance of triploid brook trout Salvelinus fontinalis - Flajšhans, Martin; Kašpar, Vojtěch; Prchal, Martin; Musatova, Iryna; Prášková, Eva; Kašpar, Jan; Hubálek, Martin (Frontiers in Animal Science, 2025)
This study analyses diploid and hydrostatic-pressure-induced triploid brook trout (Salvelinus fontinalis) sampled from a fish farm before (360 days post-hatch, d.p.h.) and during the normal time of sexual maturation for pan-sized market fish (555 and 667 d.p.h.). Biometric indices and slaughtering traits of examples of both ploidy levels were compared and their genomic heterozygosity and gonadal development were evaluated to assess the possible link between these two parameters and growth performance. At 555 d.p.h., triploids – irrespective of sex – had greater carcass yield than their diploid conspecifics. At 667 d.p.h., all triploids (females, males and intersex fish) were significantly larger and heavier and had far lower gonadosomatic indices than their diploid conspecifics; however, in terms of carcass and fillet yields these differences were not as notable. Delayed gonadal growth in triploids was confirmed. Microsatellite analysis at five polymorphic loci suggest that triploids could have higher levels of heterozygosity than their diploid counterparts, a trend in multilocus heterozygosity that was consistent in all three age groups. Nevertheless, the link between heterozygosity and body weight was inconclusive. Suppressed gonadal development seems to be more probable explanation for the improved growth performance of triploids. Remarkable occurrence of intersex fish in triploids at both 555 and 667 d.p.h suggests that intersexes can commonly arise from artificial triploidization in brook trout. External appearance, biometric indices and slaughtering traits of triploid intersex were highly similar to that of triploid females.